MICROSCOPIC ORIGINS OF MACROSCOPIC PROPERTIES OF SILICATE MELTS AND GLASSES AT AMBIENT AND HIGH PRESSURE: IMPLICATIONS FOR MELT GENERATION AND DYNAMICS - Lee S.K. (My University, 2005)
Recent development and advances in solid state NMR, together with theoretical analyses using quantum-chemical calculations and statistical mechanical modeling, have allowed us to estimate and quantify the detailed distributions of cations and anions in model silicate glasses and melts with varying pressure, temperature and composition. How these microscopic, atomic-scale distributions in the melts from NMR and simulations affect the thermodynamic and transport properties relevant to magmatic processes has been extensively explored recently. Here, based on these previous studies, we present a classification scheme to quantify the various aspects of disorder in covalent oxide glasses and melts on scales of less than 1 nm. The scheme includes contributions from both chemical and topological disorder. Chemical disorder can further be divided into [1] connectivity, which quantifies the extent of mixing among framework units (often parameterized by the degree of Al avoidance or phase separation) and the extent of polymerization (mixing between framework and nonframework cations), and [2] nonframework disorder, which denotes the distribution of network-modifying or charge-balancing cations. Topological disorder includes the distribution of bond lengths and angles. We use this framework of disorder quantification to summarize recent progress on the structures of silicate melts and glasses, mainly obtained from 2D triple quantum magic-angle spinning (3QMAS) NMR, as functions of temperature, pressure, and composition.